2013
DOI: 10.7314/apjcp.2013.14.10.5941
|View full text |Cite
|
Sign up to set email alerts
|

No Relationship between the Amount of DNA Damage and the Level of hMLH1 and RASSF1A Gene Expression in Bladder Cancer Cells Treated with Cisplatin and Gemcitabine

Abstract: Tumor response to antineoplastic drugs is not always predictable. This is also true for bladder carcinoma, a highly recurrent neoplasia. Currently, the combination of cisplatin and gemcitabine is well accepted as a standard protocol for treating bladder carcinoma. However, in some cases, this treatment protocol causes harmful side effects. Therefore, we investigated the roles of the genes TP53, RASSF1A (a tumor suppressor gene) and hMLH1 (a gene involved in the mismatch repair pathway) in cell susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, study conducted by Camargo et al , indicated that no relationship was observed between the amount of DNA damage and the level of hMLH1 (a gene involved in the mismatch repair pathway) and RASSF1 (a tumor suppressor gene) in bladder cancer cells treated with cisplatin and gemcitabine. They also confirmed other alternative pathways might be involved in cisplatin and gemcitabine genotoxicity in bladder cancer cells [72]. …”
Section: Introductionmentioning
confidence: 57%
“…On the other hand, study conducted by Camargo et al , indicated that no relationship was observed between the amount of DNA damage and the level of hMLH1 (a gene involved in the mismatch repair pathway) and RASSF1 (a tumor suppressor gene) in bladder cancer cells treated with cisplatin and gemcitabine. They also confirmed other alternative pathways might be involved in cisplatin and gemcitabine genotoxicity in bladder cancer cells [72]. …”
Section: Introductionmentioning
confidence: 57%
“…To analyze morphological alterations and gene expression profiles, cells were treated for 24 h with 1.56 μmol/L gemcitabine and 1.0 μmol/L cisplatin. As shown in comet assays and trypan blue and XTT tests, these two concentrations were genotoxic but not cytotoxic in the two cell lines that were used [13].…”
Section: Experimental Designmentioning
confidence: 83%
“…Camargo et al . (2013) showed that in bladder tumor cells the RASSF1A expression is very low because of the high levels of DNA methylation. Thus, we believe that modulation of RASSF1A expression did not interfere with the antiproliferative effects of silibinin.…”
Section: Discussionmentioning
confidence: 99%